PERMASALAHAN YANG DIHADAPI KOPERASI DI INDONESIA SAAT INI - Muniroh, Muniroh; Pawenary, Pawenary; Rahmatullah, Rahmatullah (Taksasila Edukasi Insani, 2024)
This article discusses the obstacles or problems faced by cooperatives in Indonesia, from the perspective of human resources, capital, governance systems, information transparency, technological developments and competition. Despite experiencing growth in numbers, only 9.2% of the population are members of cooperatives. If we look at the contribution to GDP and the level of labor absorption, cooperatives in Indonesia are still very minimal. The aim of this research is to identify the root of the problems that hinder the competitiveness and growth of cooperatives. Improvements in Cooperative management offered include increasing member training, capital management, transparency, and fighting negative perceptions. Cooperatives must also be able to accommodate technological changes, especially digital transformation, so as to overcome competition from microfinance institutions and online platforms. Understanding these constraints will help in developing effective strategies to strengthen the role of cooperatives in the Indonesian economy. Keywords : Economy, Cooperatives In Indonesia, Management